2001
DOI: 10.1002/jmri.10014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rotator cuff and glenoid labrum using a 0.2‐Tesla extremity magnetic resonance (MR) system: MR results compared to surgical findings

Abstract: The purpose of this investigation was to evaluate the diagnostic capabilities of magnetic resonance imaging (MRI) performed using a dedicated-extremity MR system in detecting lesions of the rotator cuff and glenoid labrum. This retrospective study compared the MR results obtained in 47 patients that underwent MRI using a 0.2-Tesla extremity MR system (E-scan) to the surgical findings. MR images of the shoulder were obtained as follows: shoulder coil, T1-weighted, coronal-oblique and axial images; short Tau inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…Notably, findings from the present study are comparable to those reported for shoulder MR imaging performed using mid-and high-field-strength MR systems. Additionally, our results are similar to those reported by Shellock et al (3), that also utilized an extremity MR system (sensitivity, 89%; specificity, 100%) and, as such, extend the experience of the use of this scanner to a multi-center study. With regard to the false negative rotator cuff examinations, most of these occurred at one orthopedic MRI facility (Oklahoma City, OK) and, thus, may be related to the particular surgical technique, diagnostic criteria, or patient population associated with this site.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Notably, findings from the present study are comparable to those reported for shoulder MR imaging performed using mid-and high-field-strength MR systems. Additionally, our results are similar to those reported by Shellock et al (3), that also utilized an extremity MR system (sensitivity, 89%; specificity, 100%) and, as such, extend the experience of the use of this scanner to a multi-center study. With regard to the false negative rotator cuff examinations, most of these occurred at one orthopedic MRI facility (Oklahoma City, OK) and, thus, may be related to the particular surgical technique, diagnostic criteria, or patient population associated with this site.…”
Section: Discussionsupporting
confidence: 91%
“…The radiologists were not provided instructions or guidance with regard to specific criteria to use in interpreting the MR images, nor were concessions made for the low-field-strength MR images. However, standard, previously described, well-accepted interpretation criteria were used (1)(2)(3)(4)(5)(12)(13)(14)19). A partial rotator cuff tear was designated as an incomplete tendon defect that was outlined by high signal intensity on MR images with T2-weighted contrast.…”
Section: Interpretation Of the Mr Imagesmentioning
confidence: 99%
See 3 more Smart Citations